Optimal Tensile Properties of Biocomposites Made of Treated Amazonian Curauá Fibres Using Taguchi Method - Pino,Gilberto García del (2021)
Abstract Natural fibres have many advantages over synthetic ones, making them attractive for reinforcing polymer materials. This work evaluates the use of an Amazonian plant, namely Curauá (Ananas erectifolius), as a reinforcement phase of biocomposites fabricated by cold pressing. Curauá fibres have been shown to be a promising fibre for composite materials, especially due to their higher elastic modulus than other plant species. An L9 Taguchi design is used to investigate the effect of fibre fraction, NaOH concentration and immersion time on the tensile properties of biocomposites. Statistical models are able of predicting and revealing the optimal composition of the biocomposites. The tensile strength of Curauá biocomposites is significantly affected by the fibre fraction, followed by the factors of immersion time and NaOH concentration. High tensile strength is obtained by adding 25 wt.% of Curauá fibres treated under different conditions. There is an interaction between NaOH concentration and the immersion time; a higher concentration requires less time or vice versa to achieve ideal roughness, promoting strong fibre/matrix adhesion.